GAMBARAN SELF-COMPASSION PADA MAHASISWA KEPERAWATAN TINGKAT SATU [DESCRIPTION OF SELF-COMPASSION IN FIRST YEAR NURSING STUDENTS] - Meyliana Megawati Hartono; Monika Kristin Aritonang; Maya Ariska; Veronica Paula; Novita Susilawati Barus (Universitas Pelita Harapan, 2021)
Self-compassion is extending compassion to one’s self by seeing failure as a positive thing not to blame yourself. Compassion represents six main components, namely self-kindness, self-judgment, common humanity, isolation, mindfulness, and over identification. As a nursing student it is important to be able to apply self-compassion to herself before becoming a nurse. It can be seen that first year nursing students at Private University in west Indonesia come from various regions throughout Indonesia, where culture is one of the factors that affect the self-compassion they have. Research Objectives to determine the level of self-compassion in first- year nursing students at Private University in west Indonesia. This study uses quantitative descriptive design methods. The sampling technique used total sampling with a total of 216. The questionnaire used in this study is the Self-compassion Scale (SCS) with a total of 26 questions. The description of self-compassion possessed by first year nursing students at Private University in west Indonesia is categorized high (95%) so that it can be said that self-compassion possessed by first year nursing students can treat a person and yourself well and understand each person's shortcomings. The next researcher can conduct qualitative research to all nursing students and nurses to find out their self-compassion.BAHASA INDONESIA Self-compassion merupakan belas kasih kepada diri sendiri dengan memandang kegagalan sebagai perihal positif untuk tidak menyalahkan diri sendiri. Belas kasih memiliki enam komponen utama yaitu self-kindness, self-judgment, common humanity, isolation, mindfulness, dan over identification. Sebagai mahasiswa keperawatan penting untuk dapat menerapkan self-compassion pada dirinya sendiri, sebelum menjadi perawat. Dapat diketahui mahasiswa keperawatan tingkat satu Universitas Swasta Indonesia Bagian Barat berasal dari berbagai daerah di seluruh Indonesia, dimana budaya merupakan salah satu faktor yang mempengaruhi self-compassion yang dimiliki. Tujuan Penelitian untuk mengetahui tingkat self-compassion pada mahasiswa keperawatan tingkat satu Universitas Swasta Indonesia Bagian Barat. Penelitian ini menggunakan metode desain deskriptif kuantitatif. Teknik pengambilan sampel menggunakan total sampling dengan jumlah 216 responden. Kuesioner yang digunakan dalam penelitian ini adalah Self-compassion Scale (SCS) dengan jumlah 26 soal. Hasil Penelitian menunjukkan gambaran self-compassion yang dimiliki mahasiswa keperawatan tingkat satu Universitas Swasta Indonesia Bagian Barat dikategorikan tinggi (95%) sehingga dapat dikatakan self-compassion yang dimiliki mahasiswa keperawatan tingkat satu dapat memperlakukan seseorang dan diri sendiri secara baik serta memahami kekurangan setiap orang. Peneliti selanjutnya dapat melakukan penelitian secara kualitatif kepada semua mahasiswa keperawatan maupun perawat untuk mengetahui self-compassion yang dimiliki.